Morphological characterization within some Algerian populations of Trifolium striatum L. (Fabaceae) - Issolah R.; Abdelguerfi A. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Within the framework of the evaluation and utilization of the plant genetic resources having a fodder and pastoral interest in Algeria, a morphological characterization was done on three Algerian populations Trifolium Striatum L. This species is regarded as quite scarce in Algeria. Several characteristics relating to plant vegetative and generative such as, fruiting heads, pods and seeds were studied. The ecological factors (rainfall, altitude) as well as geographical coordinates (latitude and longitude) of the population natural environment were taken into account during the statistical analysis. Preliminary results showed the existence of an intraspecific variation. Width of the fruiting heads characteristic was found to be particularly interesting for the taxonomic level and should deserve a special attention. The variation noticed in some characteristics of the plant, maximum height, maximum width, winter daily growth rate, length of the fruiting heads, would be linked to longitude and latitude parameters of the natural habitat of the populations. The conservation, the valorization and the development of this fodder legume, adapted to humid regions with a lot of rainfall in Algeria, could contribute towards the natural enrichment of soils with nitrogen fixation and the improvement of the living standards of the local communities through the expansion of livestock farming.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)